A Diagnostic Study on the Use of Vocabulary Learning strategies for English Majors in China - Bao, Lina (Pacific International Journal, 2023)
This research utilizes a descriptive research design to investigate the use of vocabulary learning strategies among English majors and identify the potential reasons for their difficulties in learning vocabulary. The study aims to describe the relationship between these reasons and second language vocabulary acquisition. A questionnaire, consisting of 62 items selected from the Vocabulary Learning Questionnaire (VLQ) 6.4 published by Gu and Johnson (1996), was administered to 115 sophomores majoring in English. The questionnaire was used to determine the types of vocabulary learning strategies employed by the participants, as well as the most and least frequently used strategies. The results indicate that English majors surveyed were moderate users of vocabulary learning strategies. Inferencing strategies were found to be the most commonly used, while Encoding strategies were the least used. After analyzing the participants' vocabulary learning strategies, the study proposes to improve their mother tongue competence to enhance their thinking ability, which is an essential factor in learning English vocabulary. Furthermore, the study suggests that the lack of mother tongue competence courses in higher education and the absence of effective vocabulary learning strategy guidance in the learning process are potential reasons for the difficulties experienced by English majors in vocabulary learning.